2018
DOI: 10.1038/s41561-018-0144-2
|View full text |Cite|
|
Sign up to set email alerts
|

Earthquake nucleation and fault slip complexity in the lower crust of central Alaska

Abstract: Supplementary Tables 1-5, and Supplementary Text S1 The 2015 VLFE spectra as a sum of smaller events It is possible to model the 2015 M W 3.8 VLFE as the sum of about 10 M W 3.2 earthquakes occurring over the course of about 10 seconds, following the approach Gomberg et al. (2016) used to model VLFEs as sums of much smaller LFEs. To see this, imagine the VLFE is the sum of N subevents, all of which have moment M 0s and corner frequency f cs , and source spectra

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(94 citation statements)
references
References 54 publications
1
92
1
Order By: Relevance
“…The model might imply an accelerating crescendo of seismicity or an emergent initiation of seismic waves. However, other than a few notable cases (Bouchon et al, 2011;Tape et al, 2013;Tape et al, 2018) by fault sections with larger L c . In this model, brittle patches can rupture to create small events that, in some cases, ignite dynamic rupture in the surrounding fault and cause larger ruptures without a large nucleation.…”
Section: Preslip Model: Large Nucleation On the Order Of Kilometersmentioning
confidence: 94%
See 2 more Smart Citations
“…The model might imply an accelerating crescendo of seismicity or an emergent initiation of seismic waves. However, other than a few notable cases (Bouchon et al, 2011;Tape et al, 2013;Tape et al, 2018) by fault sections with larger L c . In this model, brittle patches can rupture to create small events that, in some cases, ignite dynamic rupture in the surrounding fault and cause larger ruptures without a large nucleation.…”
Section: Preslip Model: Large Nucleation On the Order Of Kilometersmentioning
confidence: 94%
“…The model might imply an accelerating crescendo of seismicity or an emergent initiation of seismic waves. However, other than a few notable cases (Bouchon et al, ; Tape et al, ; Tape et al, ), such observations are rarely reported. This model also has trouble accounting for observations that small and large earthquakes initiate and grow similarly (McLaskey & Lockner, ; Okuda & Ide, ; Uchide & Ide, )…”
Section: Scaling Up To Natural Faultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Theoretical models and observational evidence suggest that the onset of instabilities responsible for earthquakes, landslides, and volcanic eruptions is often preceded by slowly evolving, low‐amplitude initiation phases (Bouchon et al, ; Brenguier, Campillo, et al, ; Johnson & Jia, ; Scuderi et al, ; Tape et al, ). Both high temporal resolution and high precision measurement of crustal deformation are therefore crucial for hazard prediction and early warning.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, detecting nucleation processes for natural faults by means of seismological and geodetic observations remains unsuccessful. Although several observations reported preceding slip before some earthquakes (e.g., Bouchon et al, 2011;Kato et al, 2012;Tape et al, 2018), whether the reported slow slip events are the nucleation processes of mainshocks is an open question.…”
Section: Introductionmentioning
confidence: 99%